Descriptive versus general praise with and without edibles for acquisition in young children. (4th December 2021) - Kamana, Bertilde U.; Dozier, Claudia L.; Foley, Elizabeth A.; Hubbs, Amber N.
Abstract: Previous research comparing the effects of descriptive and general praise on the acquisition of skills has yielded mixed outcomes. We attempted to replicate extend previous research by (a) isolating the effects of the different types of praise for acquisition of skills in eight preschool children and (b) determining child preference for the different types of praise. However, only two participants consistently acquired target skills (with negligible differences across the different types of praise); six of the eight participants did not consistently acquire target skills with either type of praise. Therefore, we added edibles to increase the efficacy of praise for these six participants. Results showed that all six participants acquired more skills when edibles were added. Furthermore, two of the six participants for whom we added edibles showed acquisition under particular conditions after a history with edibles. Results of the preference evaluation showed idiosyncratic outcomes across the seven participants with whom it was conducted.